алгебра 7 класс решебник ответы гдз

Номер 752

Условие:

Упростите выражение:
а) 5(4x2 - 2х + 1) - 2(10x2 - 6x - 1);
б) 7(2у2 - 5у - 3) - 4(3y2 - 9у - 5);
в) a(3b - 1) - b(a - 3) - 2(ab - а + b);
г) x2(4 - у2) + y2(x2 - 7) - 4х(х - 3).

 

Ответ:

а) 5 • (4x2 - 2х + 1) - 2 • (10x2 - 6x - 1) = 20x2 - 10x + 5 - 20x2 + 12x + 2 = 2x + 7;
б) 7 • (2у2 - 5у - 3) - 4 • (3у2 - 9у - 5) = 14у2 - 35y - 21 - 12у2 + 36y + 20 = 2у2 + y - 1;
в) a • (3b - 1) - b • (a - 3) - 2 • (ab - а + b) = 3ab - a - ab + 3b - 2ab + 2a - 2b = a + b;
г) x2 • (4 - у2) + у2 • (x2 - 7) - 4х • (х - 3) = 4x2 - x2y2 + x2y2 - 7у2 - 4x2 + 12x = -7у2 + 12x.